Debt callability and investment incentives - Schall, Lawrence D.; Siegel, Andrew F. (Journal of Corporate Finance, 2016)
Contrary to existing theory, even in perfect markets (with symmetric information, no taxes, and competitive, transaction costless capital markets) callable debt can induce investment incentives that are inferior (as well as superior) to those induced by non-callable debt, the outcome depending on cash flow and interest rate distributions. We derive necessary conditions for callable debt to induce inferior investment decisions, and define the “Call-Default Condition” as the cash flow distortion where calling prevents default that would have occurred with non-callable debt. These results complicate the argument that investment incentives explain the presence of the call provision in debt contracts.